Why Has the Euro Been Falling? - Hans-Werner Sinn; Frank Westermann (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper reconsiders the determinants of the exchange rate by studying the historical episode after the fall of the Iron Curtain. Testing a modified portfolio balance model, we attribute the strength of the deutschmark in the early nineties and the puzzling decline of the euro during its virtual existence to changes in the demand for deutschmarks in eastern Europe and to variations in the demand for black money balances in Europe as a whole. We reject the view that the strength of the dollar and the weakness of the euro reflect the prosperity of the US and the weakness of the European economy on both theoretical and empirical grounds.
Keywords: 330